The rediscovered writings of Rose Wilder Lane, literary journalist - Lane, Rose Wilder, 1886-1968 (University of Missouri Press, 2007)
"Famous as the editor of her mother's Little House books, Rose Wilder Lane worked for fifty years as a literary journalist, traveling widely and commenting on a broad range of topics. Amy Mattson Lauters has collected examples of Lane's literary nonfiction articles that have been unavailable since their original publication"--Provided by publisher.